Role of Teachers in the Promotion of Activity Based Learning at Primary Level - Sumayya Nisar; Dr. Hafiz Muhammad Irshadullah; Dr. Abdul Ghaffar (Dialogue Social Science Review (DSSR), 2025)
Role of teachers in the promotion of activity based learning at primary level was a novel study. In this study these research objectives were used: (1) To investigate instructors’ practical application for activity-based learning at primary level; and (2) To find out the effects of activity-based learning at primary level. In this research work the following research questions were tested: (1) What are teacher’s practical application for activity based learning at primary level? and (2) What are the effects of activity-based learning at primary level? All the (20) Private Primary Schools in Sheikh Maltoon Mardan were the population in this study. A sample of (12) Private Primary Schools in Sheikh Maltoon Mardan was selected randomly. In which the following respondents were included. A closed-ended questionnaire with three options was developed, validated, reliability was calculated @ 0.80, and the study was delimited to Sheikh Maltoon in District Mardan. It is concluded that majority of teachers are using activity-based learning. Teachers encouraging participation, plan activities, simplify a challenging subject, make a topic clear, and boost students' creativity. It was suggested that teachers concentrate on activity-based learning based on the findings. For them to function well in teaching and learning environments, the authorities must provide them with the necessary training.